PENGARUH EPS TERHADAP RETURN SAHAM PADA BANK SYARIAH INDONESIA (BSI) DI BURSA EFEK INDONESIA (BEI) PERIODE 2021 - Jaza'i, Ridwan (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2025)
This study seeks to assess the impact of Earnings Per Share (EPS) on stock returns at Bank Syariah Indonesia (BSI) on the Indonesia Stock Exchange (IDX) for the year 2021. The research methodology employed is quantitative (Exploratory Research). The subject of this study is Bank Syariah Indonesia (BSI). The research utilises secondary data, specifically the financial accounts of Bank Syariah Indonesia (BSI) until 2021. The analytical method employs multiple linear regression. The findings of this study demonstrate that the EPS variable exerts a partial yet considerable influence on stock returns.